Common prosperity level evaluation: A comprehensive method based on probabilistic linguistic ordered weighted distance measure, prospect theory, and TOPSIS - Zhang, Erhua; Yu, Feifan; Jiang, Ting; Zeng, Shouzhen; Wang, Dandan (Frontiers in Psychology, 2023)
Common prosperity is a major research project in China, and the scientific measurement and evaluation of common prosperity is very important. In this study, firstly, we constructed a comprehensive evaluation index system for the common prosperity level (CPL). We then developed an evaluation model of CPL based on prospect theory, probabilistic linguistic ordered weighted distance measure, and the TOPSIS method, wherein we used a probabilistic linguistic term set (PLTS) to describe the uncertainty and complexity of the assessment process. Above all, we use prospect theory to reflect the preferences of decision makers to meet the unique needs for the evaluation of common prosperity. Moreover, we applied the proposed evaluation index system and model to evaluate the CPL of Zhejiang Province, China's first common prosperity demonstration zone, as an example to conduct relevant research. Finally, we propose specific suggestions for improving the development of common prosperity.